Philosophy and Design
XIV, 360 p.
Keywords: This volume provides the reader with an integrated overview of state-of-the-art research in philosophy and ethics of design in engineering and architecture. It contains twenty-five essays that focus on engineering designing in its traditional sense, on designing in novel engineering domains, including ICT, genetics, and nanotechnology, designing of socio-technical systems, and on architectural and environmental designing. These essays are preceded by an introductory text structuring the field of philosophy and ethics of design in engineering and architecture as one in which a series of similar philosophical, societal, and ethical questions are asked. This volume enables the reader to overcome the traditional separation between engineering designing and architectural designing. The emerging discipline of designing socio-technical systems is shown to form an intermediate between engineering and architecture to which the philosophical and ethical analyses of both domains apply. This volume thus announces a challenging cross-fertilization between the philosophy and ethics of engineering and of architecture that will lay down the integrated ground works for the renewed interests in the importance of design in modern society. "Philosophy and Design: From Engineering to Architecture is a significant contribution to the expanding field of design studies. It brings questions of design into philosophy and thereby brings diverse philosophical perspectives to bear on conceptual, methodological, epistemological, metaphysical, and ethical issues of design. It is also the first collection of philosophical papers to bridge the divide between critical reflections on design in engineering and in architecture. After the publication of this well edited collection, it will be difficult for philosophy to ignore design as a theme as worthy of attention as such phenomena as scientific theory, aesthetic creativity, or political law." Carl Mitcham, Professor of Liberal Arts and International Studies at the Colorado School of Mines and author of the authorative monograph "Thinking through Technology (1994)".